Pengaruh Perbedaan Konsentrasi Pupuk Organik Cair tehadap Produksi Bawang Merah (Allium ascalonicum L) - Setiyowati, Setiyowati; Haryanti, Sri; Hastuti, Rini Budi (Bioma : Berkala Ilmiah Biologi, 2010)
Shallot is one an important of vegetable comodity, both in economic value and nutrition ingredients. One of an effort to support the increasing of shallot yield with plantation technology by giving organic liquid fertilizer. The experiment we studied to find out the effect of organic liquid fertilizer with different consentration on yield of shallot. The experiment used Completely Randomized Design consisted 6 consentration of organic liquid fertilizer 0 ml/L (P0), 1 ml/L (P1), 2 ml/L (P2), 3 ml/L (P3), 4 ml/L (P4), 5 ml/L (P5) with 4 replication. The results show that consentration of 4 ml/L organic liquid fertilizer is increas the number of bulb and consentratin of 5 ml/L is increas in tuber wet weight.